Exploring the shortcomings of the Iranian MSRT English Proficiency Test - Ghorbani, Mohammad Reza; Abbassi, Hadi; Mohamed Razali, Abu Bakar (Universiti Putra Malaysia Press, 2021)
The Iranian Ministry of Science, Research, and Technology (MSRT) English Proficiency Test (EPT) has been in use since 1992. While the MSRT-EPT is generally claimed to be reliable, valid, and practical, it does not assess speaking and writing skills. In this exploratory study, a qualitative approach was used to examine the MSRT-EPT testtakers experiences and language education experts’ beliefs about the test as well as their congruence with each other through semi-structured telephone interviews. Convenience and purposive sampling procedures were used to select 15 participants. Inductive coding method was applied to determine invariant constituents. Then, the constituents were reduced to categories, and finally the categories were clustered into 11 themes. Dependability and validity of the study were established through triangulation, inter-coder agreement, and member checking technique. The problems associated with the MSRT-EPT and a lack of productive skills included a lack of correspondence between the test content and Ph.D. Candidates' needs, negative washback effect, non-theory-based content, inappropriate listening conditions, and a lack of test items originality. On the other hand, the candidates’ and experts’ perspectives were highly congruent. In light of these findings, the importance of designing a more comprehensive test including all facets of the language proficiency construct was highlighted, and some suggestions were made for future research.